1992
DOI: 10.1002/jlb.52.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of murine IP-10 mRNA following systemic treatment with interferon γ

Abstract: We have examined the tissue distribution of 10-kd inflammatory protein (IP-10) mRNA expression in C57Bl/6 mice injected intravenously (i.v.) with various inflammatory stimuli. IP-10 mRNA was strongly induced by interferon-gamma (IFN-gamma) in liver and kidney but only poorly in skin, heart, and lung. IFN-gamma had nearly equivalent access to these tissues as indicated by the distribution of radiolabeled recombinant IFN-gamma 1 h after injection. The time course of IP-10 mRNA appearance was rapid and transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…late clearance of the virus. Considered together with the earlier reports that CXCL10/IP-10 is induced by both IFN-␣␤ and IFN-␥ (20,24,(67)(68)(69), our findings that both CXCR3 Ϫ/Ϫ and CXCL10/ IP-10 Ϫ/Ϫ mice are more susceptible to dengue virus underscores the importance of characterizing the mediators situated downstream of IFNs in the host defense against primary dengue infection.…”
Section: Discussionsupporting
confidence: 82%
“…late clearance of the virus. Considered together with the earlier reports that CXCL10/IP-10 is induced by both IFN-␣␤ and IFN-␥ (20,24,(67)(68)(69), our findings that both CXCR3 Ϫ/Ϫ and CXCL10/ IP-10 Ϫ/Ϫ mice are more susceptible to dengue virus underscores the importance of characterizing the mediators situated downstream of IFNs in the host defense against primary dengue infection.…”
Section: Discussionsupporting
confidence: 82%
“…Mouse tissue was homogenized for total RNA extraction by the guanidinium isothiocyanate-CsCl method as described previously (16,17). The levels of cytokine and chemokine mRNA were determined either by Northern hybridization using radiolabeled cDNA fragments as described previously (16,17) or by use of the RiboQuant RPA system (BD PharMingen, San Diego, CA) according to the manufacturer's instructions.…”
Section: Rna Preparation Northern Hybridization and Rnase Protectiomentioning
confidence: 99%
“…The levels of cytokine and chemokine mRNA were determined either by Northern hybridization using radiolabeled cDNA fragments as described previously (16,17) or by use of the RiboQuant RPA system (BD PharMingen, San Diego, CA) according to the manufacturer's instructions. Plasmids containing KC, MIP-2, and GAPDH cDNAs were prepared as described previously (18,19).…”
Section: Rna Preparation Northern Hybridization and Rnase Protectiomentioning
confidence: 99%
“…Because gene expression of these three ELR Ϫ CXC chemokines is induced in tissue-, cell type-, and stimulus-specific fashions (10,(12)(13)(14), the effect of CXCL10 neutralization differs depending on the pathogens or immunogens and the target organs affected. We have shown that CXCL10 is selectively induced in dendritic cells (DCs) in the draining lymph nodes (LNs) to retain Th1 cells, maintaining DC-T cluster formation in acute experimental autoimmune encephalomyelitis (EAE) (15) and heat-killed Propionibacterium acnes-induced hepatitis (16).…”
mentioning
confidence: 99%